Profile of lactic acid within validity of full natural yogurt - Goncalves da Silva, Felipe Chaimsohn [UNESP]; Dalaqua, Sofia; Azevedo, Everton Cruz de [UNESP]; Campos, Glaucia Martins de [UNESP]; Raghiante, Fernanda [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
The objective of this study was to analyze the profile of lactic acid from three different brands of yogurt, integral type, marketed in the southwest region of Sao Paulo in the period of validity. pH and acidity analyzes were performed in the 15th, 30th and 45th day after the manufacture of the product. The results showed that there were no significant variations in the pH values. However, the lactic acid had greater variability in values. Despite this, all the tests remained within acceptable parameters for yogurt.
Keywords: Lactic Acid; pH; Validity; Yogurt